The Influence of Job Satisfaction and Loyalty on OCB at Hilton Garden Inn Ngurah Rai Airport - Anjani, Ayu Putu Mira Nafa; Sulistyawati, Ni Luh Ketut Sri; Jata, I Wayan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Organizational Citizenship Behavior (OCB) impacts various aspects such as job satisfaction and employee loyalty. This study aims to determine the effect of employee satisfaction and loyalty on OCB at Hilton Garden Inn Ngurah Rai Airport. The research population includes the employees of Hilton Garden Inn, with a sample of 76 respondents using a census sampling method. The analysis was conducted using simple linear regression and SPSS version 26 for Windows as the analytical tool. The results of this study indicate that both job satisfaction and employee loyalty have a positive and significant influence on organizational citizenship behavior, both partially and simultaneously. The contribution of job satisfaction and loyalty to organizational citizenship behavior is 56.5%.